Selection of New Zoysiagrass Genotypes for Golf Course Fairways, Greens, and Tees in the Upper Transition Zone - Manoj Chhetri; Jack Fry; Megan Kennelly (Kansas Agricultural Experiment Station Research Reports, 2021)
A set of 70 experimental zoysiagrass genotypes along with three standards, ‘Meyer,' ‘Innovation,' and ‘KSUZ 1201,' were evaluated for turf performance in the northern transition zone. The genotypes were previously selected from a set of 935 progeny that resulted from pairwise crossings of cold-hardy zoysiagrass parents with fine-textured, under-utilized zoysiagrasses. All 70 progeny survived the winter of 2019–2020 and thus were evaluated based on their turf performance. The preference of selection was based first upon spring green up ratings, followed by leaf texture (finer preferred), vigor, turf quality, and wilt during dry down. A total of 20 best progeny were selected and harvested for propagation on October 12, 2020. Only one genotype, ‘6844-31’ had a texture rating of 8.0 (1 to 9 scale; 9 = finest texture) and four other genotypes had texture ratings higher than 7.0 among the selected 20 best progeny. The progeny will be established in larger replicated plots at several locations including Kansas State University Olathe Horticulture Center, Olathe, KS, starting in the summer of 2021
Keywords: golf course turf; warm-season grasses